Pemerolehan Bahasa Pada Anak Usia 3 Tahun 3 Bulan dalam Kajian Mean Length Of Utterance dan Aspek Fonologi - Fitri, Amalia; Setiawan, Hendra (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is motivated by language acquisition in children which is influenced by age and normal stagedevelopment. This study sought to determine the average length of utterances and phonological aspects of children aged 3 years and 3 months who daily use their first language, namely Indonesian.This research approach uses a qualitative research approach and descriptive methods. The main source for this researchis a girl named Altha aged 3 years 3 months. The source of supporting data is Altha's biological father and mother. Researchers collected data for approximately one month, starting from an interview with Altha's biological mother and continuing with direct observation. The data collection technique in this research uses the observation technique. Data obtained from recording results. Next, the research data was analyzed through three activities in stages, namely data reduction, data presentation, and drawing conclusions or verification.The research results prove that the acquisition of Altha is in the normal category at stage VII (3.0 - 3.5) at the age of around 35 – 39 months. Based on the phonology results, Altha can master vowel letters, such as a, i, u, e, o,eh and have mastered consonant letters or alphabets such as /c/, /b/, /m/, /y/, /g/, /ŋ/, /e/. However, there are still some letters that are difficult to pronounce, such as /s/, /l/, and /r/. Therefore, based on the calculation results, the average length of Altha's utterances is included in the normal or very good category according to Brown's theory.